STUDENT OF PHARMACY, NURSE, PUBLIC HEALTH, NUTRITIONIST AND PHYSICAL EDUCATION READINESS TOWARD INTERPROFESSIONAL EDUCATION (IPE) - Utami, Vitis Vini Fera Ratna; Satibi, Satibi; Kristina, Susi Ari; Prabandari, Yayi Suryo (Universitas Muhammadiyah Magelang, 2024)
The implementation of interprofessional education (IPE) into higher education curricula is a significant method for creating professionals with the skills necessary for interprofessional collaboration (IPC), including those in the health sciences, nursing, pharmacy, and nutrition. Due to the changes in health services, which are becoming more integrated, it is vital to have the capacity for interprofessional collaboration. The readiness of the pupils for IPE must be assessed before to its implementation in order to identify the subjects that should be highlighted at that time. This research is a cross-sectional study using descriptive analysis method. The distribution of respondents was as all in 4th semester students, consist of department of Pharmacy (n=92), department of Nursing (n=88), department of Public Health (n=95), department of Nutrition (n=66) and department of Physical Education (n=42) in Faculty of Health Sciences. Questionnaire data collection was carried out online. The independent variable that is measured is the student's readiness for Interprofessional Education. The results findings there is a significant difference between the readiness of students in Nurse department and students of all department. The nurse department received the highest score (score = 68.47) and the Health Education received the lowest score (score = 65.59). But all department receive score > 80% of the total score. There is still room for improvement in the areas related to the value of learning together in practical situations